2007
DOI: 10.1007/s10533-007-9076-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of ammonium and phosphate release from intertidal and subtidal sediments of a shallow coastal lagoon (Ria Formosa – Portugal): a modelling approach

Abstract: During an annual cycle, overlying water and sediment cores were collected simultaneously at three sites (Tavira, Culatra and Ramalhete) of Ria Formosa's intertidal muddy and subtidal sandy sediments to determine ammonium, nitrates plus nitrites and phosphate. Organic carbon, nitrogen and phosphorus were also determined in superficial sediments. Ammonium and phosphate dissolved in porewater were positively correlated with temperature (P < 0.01) in muddy and sandy sediments, while the nitrogen-oxidized forms had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 42 publications
3
35
0
Order By: Relevance
“…As nitrification, ammonium regeneration in sediments appears to be correlated with oxygen with steadily decreasing rates at decreasing oxygen concentrations (Chapelle, 1995;Serpa et al, 2007). Thus, we conclude (from the sparse data at hand) that the negative correlation of deep layer ammonium concentrations with seawater CO 2 was more likely caused by reduced ammonium regeneration rates rather than higher nitrification rates in the 3× compared to the 2× and 1× CO 2 mesocosms.…”
Section: Inorganic Nutrient Uptake and Organic Materials Build-upmentioning
confidence: 73%
“…As nitrification, ammonium regeneration in sediments appears to be correlated with oxygen with steadily decreasing rates at decreasing oxygen concentrations (Chapelle, 1995;Serpa et al, 2007). Thus, we conclude (from the sparse data at hand) that the negative correlation of deep layer ammonium concentrations with seawater CO 2 was more likely caused by reduced ammonium regeneration rates rather than higher nitrification rates in the 3× compared to the 2× and 1× CO 2 mesocosms.…”
Section: Inorganic Nutrient Uptake and Organic Materials Build-upmentioning
confidence: 73%
“…16,18,45 Falcão 16 and Serpa et al 35 observed larger values of ammonium during the summer in Ria Formosa. Our results agree with this pattern but these high values were sustained after summer.…”
Section: Nutrient and Chlorophyll Conditions In The Sedimentsmentioning
confidence: 93%
“…Total benthic concentrations were also calculated, considering that sediment surface is approximately constituted by 50% of sandy sediments and 50% of muddy sediments. 35 Concentrations of pelagic chlorophyll were converted to mg m À2 units so that they could be easily comparable with MPB concentrations. Pelagic chlorophyll amounts of about 132 kg (or 2.49 mg m…”
Section: Chlorophyllmentioning
confidence: 99%
“…Mussels and barnacles ----: y = 0.25 -0.02 t; r 2 = 0.72. Manila clams, mussels and barnacles ---: y = 0.32 -0.035 t; r 2 = 0.78 noted during summer as compared to cooler seasons (Serpa et al 2007). Ammonium was not supplied to intertidal sediments via ground water as indicated by the pore water profiles; however, there was greater sorption of ammonium by surficial sediments of farmed as compared to reference sites.…”
Section: Ammoniummentioning
confidence: 96%
“…Enoksson 1993, Twichell et al 2002, Hou et al 2003, Burgin & Hamilton 2007, Fulweiler et al 2007, Serpa et al 2007). Perhaps receiving less attention although no less important are iron and phosphorus (reviewed in Newell 2004).…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%